ESL Students Anxiety in English as a Second Language Learning from The Perspective of Linguistic Skills - Ahmad, Azhar; Rao, Imama Sabir; Rao, Muniba Sabir (Pakistan Journal of Humanities and Social Sciences, 2023)
The present research primed to divulge the state of ESL students’ anxiety while learning linguistic skills in the scenario of ESL classrooms in Pakistani context. The one hundred fifty ESL undergraduates were selected from three well-known private universities of the Lahore city. For ethical concern institution and contributors’ information was concealed. The researchers visited the concerned department of the universities with the permission of their head of the departments and collected data by using random sampling. The questionnaire was divided among these ESL students which was contain on three parts, first part comprises demographic information of the participants, the sconed part contains on six close ended questions, while the third part contains on one open ended question. Data was composed through the instrument of questionnaire and congregated data was later analysed by using SPSS software and presented in figures, graphs and tables. The findings exhumed that ESL undergraduates undergoing anxiety owing to lack of motivations, interactions from instructors and fellows and unsupportive environments. The researchers suggested some recommendations to decrease the anxiety related to the four skills of English language. Key Words Foreign language anxiety, ESL classrooms, ESL undergraduates, Anxiety in productive skills, Anxiety in receptive skills.